The Impact of Family Caregiver Burden on Stroke Patient Care Behavior - Darussalam, Miftafu; Adeana Putri (HEALTHY BEHAVIOR JOURNAL, 2025)
Background: Stroke prevalence in the Special Region of Yogyakarta is ranked second highest in Indonesia, with a prevalence of 14.6%. The highest prevalence is in the city of Yogyakarta at 1.50%. In cases of stroke, family caregiver s must accompany the patient for up to 24 hours to meet all the patient's needs. The role of family caregiver s aims to restore the quality of life of stroke patients and improve the therapeutic efforts of patients. Objective: The research aims to determine the relationship between family caregiver burden and behavior in caring for stroke patients at the Yogyakarta City Hospital. Methods: The research is quantitative with a descriptive correlative design and a crosssectional approach. The number of samples used was 39 respondents selected using purposive sampling techniques. Data collection used the Zarit Burden Interview Questionnaire and the Family caregiver Behavior Questionnaire, which have been validated and are reliable. Data analysis in this study used univariate and bivariate analysis. Results:  The results showed that family caregiver burden is related to behavior in caring for stroke patients (r=-0.335; p=0.037). The distribution of family caregiver burdens includes no burden 43.6%, light burden 51.3%, moderate burden 5.1%, while family caregiver behavior in the category of less 5.1%, family caregiver behavior in the category of sufficient 69.2%, and family caregiver behavior in the category of good 25.6%. Conclusion: Good family caregiver behavior in caring for stroke patients has a positive impact on the patients themselves. For family caregiver s who are detected to have a high burden, it is hoped that they can consult on how to overcome it so that the quality of life of stroke patients and family caregiver s can improve.